Efek Antiinflamasi dan Antipiretik Ekstrak Batang Bajakah Tampala (Spatholobus littoralis Hassk) pada Mencit (Mus musculus L.) - nofri - zayani; Bela Novita Amaris Susanto; Eva Marsepa (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2022)
Exploration of the plants used to treat inflammation and fever continues to grow. One of the plants with great potential is Bajakah tampala (Spatholobus littoralis Hassk). Phytochemical test results showed bajakah contains flavonoids, tannins, saponins, phenolics, and terpenoids that function as anti-inflammatory and antipyretic so as to reduce inflammation and fever. The purpose of this study was to examine the anti-inflammatory effect of Bajakah stem extract (EBB) on the edema area and leukocyte numbers, as well as its antipyretic effect on the rectal temperature of mices. Total experimental study design with a completely randomized factorial design consisted of 5 treatments (EBB doses 0, 25, 50, 100 and aspirin 80 mg/kg) and 4 replications. EBB was extracted by maceration with 70% ethanol. Mices used were 20 healthy males, aged 13-14 weeks, and weighed 30-35 grams. 1% carrageenan was used to induce inflammation and baker's yeast was used to induce fever. EBB is given orally after 30 minutes of inflammation and an increase in rectal temperature. Data were analyzed by variance analysis (ANOVA) and continued with Duncan Multiple Range Test (DMRT) at 1% level. The results showed that EBB administration had an effect on reducing edema area and leukocyte numbers after 1% carrageenan induced, and the rectal temperature of mices after baker's yeast induced. In conclusion, EBB has good anti-inflammatory and antipyretic effects with the most effective dose of 25 mg/kg. Keywords: Bajakah tampala, Edema, Leukocytes, Rectal temperature